2007
DOI: 10.1590/s1516-31802007000500006
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and clinical characteristics, causal factors and evolution of a group of patients with chronic urticaria-angioedema

Abstract: CONTEXT AND OBJECTIVE: Chronic urticaria-angioedema is a common, multiple-cause complaint. The aim was to investigate the sociodemographic and clinical characteristics, causal and aggravating factors and evolution of urticaria-angioedema. DESIGN AND SETTING: This was a descriptive prospective study carried out at the Dermatology outpatient clinic of Faculdade de Medicina de Botucatu, Universidade Estadual Paulista (Unesp). METHODS: A total of 125 patients with chronic urticaria-angioedema were evaluated to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
2
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 25 publications
4
17
2
10
Order By: Relevance
“…3 The reason why a higher frequency of angioedema was found in our patients remains unclear, but it may be associated with regional iodine sufficiency, or with the fact that the ATD rate found in this study was higher (19.1%) than what was reported by Feibelmann et al (12.3%), 15 and higher than in American studies on the general population (3-10%). 8,29 The association between angioedema and ATD was evident.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…3 The reason why a higher frequency of angioedema was found in our patients remains unclear, but it may be associated with regional iodine sufficiency, or with the fact that the ATD rate found in this study was higher (19.1%) than what was reported by Feibelmann et al (12.3%), 15 and higher than in American studies on the general population (3-10%). 8,29 The association between angioedema and ATD was evident.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, they observed that CU affected patients at all ages, but particularly those between 20 and 50 years (mean age of about 35 years). 3 Hypothyroidism was the most frequent dysfunction in our sample (16.5%). Pimenta et al found a similar rate (16%) in outpatients.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Silvares et al detect arthralgia and chronic headache as the most common systemic symptoms in patients with chronic urticaria and angioedema similiarly to our study. [17] In the same study CU and angioedema were accompanying with some dermatological diseases such as fungal infection, acne vulgaris, pityriasis versicolor, xeroderma, seborrheic dermatitis and other dermatoses. [17] The most common accompanying dermatological diseases were acne vulgaris, atopic dermatitis, lichen simplex chronicus, xeroderma, pityriasis versicolor, alopecia areata, eczema, palmoplantar psoriasis and psychogenic pruritus in our study.…”
Section: Resultsmentioning
confidence: 85%
“…Silvares i sar. [18] su u prospektivnoj studiji od 125 pacijenata pokazali da se hronič-na urtikarija javlja uglavnom u žena srednje dobi od 35 godina, a kod muškaraca u dobi od 32 godine.…”
Section: Diskusijaunclassified